Janko Žel, Maistrov borec, narodnjak in prosvetni delavec - Toš, Marjan (Časopis za zgodovino in narodopisje, 2023)
Following the resounding events in Maribor on the night of 22–23 November 1918, a part of the Maribor Volunteer Regiment set out to defend the territory along the Mura River. The 6th corps of the Maister’s fighters under the command of Lieutenant Ben (Benedikt) Zeilhofer3 occupied the railway line Špilje – Radgona and on 1 December 1918, the day of the foundation of the Yugoslav State of Serbs, Croats and Slovenes (SHS)4, together with the unit of Lieutenant Commander Janko Žel, carried out a march on Cmurek and Radgona. Commander Janko Žel was personally ordered by General Maister to take Cmurek with his unit. Therefore, on 1 December 1918, he set out from Maribor by train and travelled via Špilje together with the 6th corps of the Maister’s fighters of Lieutenant Ben Zeilhofer, who had been ordered to seize Radgona. In his letter to Benedikt Zeilhfer of 29 October 1968, Janko Žel recalls how they arrived in the evening at Cmurek, where Žel was to carry out his mission. But he changed his mind and, together with Zeilhofer’s unit, continued on his way to Radgona, where there was a stronger German garrison. Janko Žel was a teacher all his life and received several awards for his dedicated work as a teacher. On 25 March 1975, he received a plaque from the Association of Volunteers – Fighters for the Northern Border 1918– 1919 in Ljubljana for his participation in the fighting for the Northern Border. After his retirement in 1946, he lived in Ljubljana, where he died on 24 November 1985. He is buried in Ljubljana’s Žale Cemetery.
Keywords: biografije; slovenski učitelji; vojaška zgodovina; Žel, Janko